Evaluation of ‘Internship Induction Programme’: an application of Kirkpatrick’s model - Choudhari, SG; Rawekar, AT; Bhagat, VM; Mudey, AB (International Journal of Medical Research and Review, 2015)
Introduction: Often, interns remain unaware of what is expected of them during internship period and work without a clear aim. Induction is a very important process but in reality in many of the medical colleges, internship induction programme is limited to mere ‘Hippocratic Oath taking ceremony’ for the interns. In this context the present study conducted with the objectives - To evaluate interns ‘Gain in learning’ through Internship Induction Program (IIP), to assess the perception of interns regarding benefits to them through IIP, to assess perception of faculty members, administrators involved in IIP regarding benefits to interns and to beneficiaries (patients) in hospital/community and to take the feedback from interns, faculties involved, about the newly launched module for IIP. Methods: Study participants were the Interns undergoing IIP(n1=166) and the faculty from varied disciplines who participated in IIP(n2=20). Study tool were the Pre & post test questionnaire for interns and feedback proforma with regard to IIP & newly launched ‘IIP Module’, both for interns and faculties. Evaluation has done as per the guidelines of Kirkpatrick’s model of programme evaluation where in first two levels of evaluation were considered. Results: Response rate was 100%. Mean Pre-test and post test scores were 6.92±2.55 and 15.03±2.92 respectively (p value<0.05). Absolute learning gain=40.55%, Learning effectiveness score=117%, Class average normalized gain=61%, Effect size=2.95. In feedback analysis for most of the parameters, the rating average was to the right side of the neutral indicating a positive feedback. Conclusion: Programme Evaluation of IIP with Kirkpatrick’s model revealed it to be successful in achieving its objective of improving knowledge and attitude of interns.